Islamic Economic Review of Bitcoin Ownership as A Digital Asset - Abdullah, Muhammad; Solehah, Siti; Romdoni, Indi Auliya (International Journal of Sharia Business Management, 2024)
Bitcoin, as a form of cryptocurrency operating within a decentralized network known as blockchain, has become a global phenomenon with increasing value and popularity. Despite offering various opportunities, Bitcoin also raises numerous questions and controversies, particularly from the perspective of Islamic economics, which has specific principles and rules regarding asset ownership, investment, and financial transactions. This study aims to analyze the status of Bitcoin ownership as a digital asset from the viewpoint of Islamic economics. The research method employed is qualitative with a literature review approach. Data were obtained through relevant literature, including journals, books, articles, and fatwas from scholars. The results of the study indicate that the extreme price volatility of Bitcoin tends to trigger excessive speculation (maisir), which is prohibited in Islamic economics as it can lead to injustice and uncertainty (gharar) in transactions. Additionaly, Bitcoin is often associated with activities that do not align with Sharia principles, such as gambling and ilegal transactions